Effect of Think-Pair-Share Instructional Strategy on Secondary School Students’ Academic Achievement in Chemistry - Franklin Nnanna Ibe; Bernadette A. Ezeliora; Chinyere F. Okafor (PT. Pusmedia Group Indonesia, 2024)
This study investigated the effect of think-pair-share instructional strategy on secondary school students’ academic achievement in Chemistry. It covered the topics; acids, bases and acid-base reactions. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The quasi-experimental design was adopted. The population of the study was 5,714 senior secondary school year one (SS1) Chemistry students in Awka Education zone in Anambra State. A sample of 192 SS 1 Chemistry students obtained using stratified and simple random sampling techniques was involved in the study. The instrument for data collection was Chemistry Achievement Test (CAT) validated by experts. The reliability of the instrument was established using Kuder-Richardson Formula 20 for CAT which yielded coefficient of internal consistency of 0.81. Data were collected by administering the instruments. The data obtained were analyzed using mean and standard deviation to answer the research questions; and analysis of covariance (ANCOVA) to test the hypotheses. The findings of the study revealed that there was significant difference in the mean academic achievement scores of the students taught Chemistry using think-pair-share instructional strategy and those taught using lecture method in favour of think-pair share instructional strategy. Moreso, there was no significant difference in the mean achievement scores of male and female students taught Chemistry using think-pair-share instructional strategy. Based on the findings, recommendations were made that seminars should be organized to orient Chemistry teachers on how to effectively use TPS instructional strategy in the teaching and learning of Chemistry. The study contributed to knowledge such that it has empirically proved and established that use of TPS improves students' academic achievement in Chemistry surpassing lecture method. The study also revealed empirically that use of TPS in teaching Chemistry enhances male and female students’ academic achievement